Study on Survival and Growth Rate of Some Variety of Fish Fry Indigo (Oreochromis sp.) The Different Size of 3-5 Centimeters - Lutviana N.D; Maheno Sri Widodo; Eric Armando (Journal of Aquaculture Development and Environment, 2020)
Tilapia has several varieties produced from cross-breeding. The results of cross-breeding produce new varieties in tilapia with their respective advantages in terms of survival and growth. But until now there has been no research on survival studies and the growth rate of some of the best Tilapia fish varieties. This study used a completely randomized design, 4 treatments 3 replications. The treatments given were (A) Gift Tilapia, (B) Red Tilapia Fish, (C) Jatimbulan Tilapia Fish and (D) Solid Tilapia Fish. Tilapia seeds maintained in treatment B (red tilapia) gave the highest survival value of 88.87% and the lowest value in treatment A (gift tilapia) and D (stocky tilapia) were 83.33%. In treatment A (Gift Tilapia) gave the highest length growth value of 1.6-1.7 cm and the highest daily weight growth rate of 0.085 gr / day, while in treatment B (Red Tilapia) gave the lowest length growth value of 1.3-1.45 cm and the lowest daily individual weight growth rate of 0.062 gr / day. Water quality parameters such as pH, DO and temperature measured during the maintenance period are in the normal range, so they do not have a significant effect on the growth of tilapia fish. The highest FCR was obtained in treatment B (Red Tilapia) with an average of 0.90 and the lowest FCR was obtained in treatment A (Tilapia Gift) with an average of 0.69.